2010
DOI: 10.1111/j.1708-8208.2008.00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Extrasinus Zygomatic Implants: Three Year Experience from a New Surgical Approach for Patients with Pronounced Buccal Concavities in the Edentulous Maxilla

Abstract: The present 3-year clinical study shows that an extrasinus approach can be utilized when placing zygomatic implants in patients with pronounced buccal concavities in the posterior maxilla. Moreover, the technique results in an emergence of the zygomatic fixture close to the top of the crest, which is beneficial from a cleaning and patient-comfort point of view.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 17 publications
2
65
0
10
Order By: Relevance
“…Great discrepancies in the results obtained by Becktor may be due to, according to the author, difficulty in maintaining optimum hygiene at the posterior palatal emergency; transversal mobility produced by functional forces when there is a lack of osseointegration and bone-implant contact at a marginal level; and the internal design of the implant, which may produce an oroantral communication. However, the extrasinus technique permits a more favourable emergence of the implant, and facilitates adequate hygiene maintenance of the area (3,10). As for the design of the implant, some authors mention that in later studies, reported rates on this complication are not as high (4,11), therefore, more conclusive studies in this area are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Great discrepancies in the results obtained by Becktor may be due to, according to the author, difficulty in maintaining optimum hygiene at the posterior palatal emergency; transversal mobility produced by functional forces when there is a lack of osseointegration and bone-implant contact at a marginal level; and the internal design of the implant, which may produce an oroantral communication. However, the extrasinus technique permits a more favourable emergence of the implant, and facilitates adequate hygiene maintenance of the area (3,10). As for the design of the implant, some authors mention that in later studies, reported rates on this complication are not as high (4,11), therefore, more conclusive studies in this area are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly or medically compromised patients may not be suitable for bone grafting because of increased surgical risk and morbidity. In these situations, when the surgeon and the patient prefer to avoid surgical reconstruction with autologous bone grafts or when this choice is not available clinically, the use of zygomatic implants is an alternative procedure for treatment of the severely atrophic maxilla (Hirsch et al, 2004;Aparicio et al, 2008;Ventorre et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…There still is no consensus on the ideal technique for placing zygomatic implants in relation to the degree of bone anchorage and implant inclination (Aparicio et al, 2008). Little is known about the quantity of zygomatic bone around zygomatic implants placed with different techniques, which could affect initial mechanical implant stability.…”
Section: Introductionmentioning
confidence: 99%
“…las cuales someten al paciente a múltiples procedimientos quirúrgicos, prolongando el tiempo de cicatrización y cuidados postoperatorios (7)(8)(9)(10)(11).…”
Section: Introductionunclassified